A Pragmatic Study of Gestural Strategies in English Political TV Interviews - Radhi, Zainab Mohammed; Ibrahim, Atyaf Hassan; Al-Obaydi, Liqaa Habeb (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Part of the substance of an utterance could be represented by gestures. There are many different perspectives on how gestures, words, and cognition relate to one another and how they could influence communication. Gestures are inferior to words because they communicate no semantic information beyond the linguistic utterances that accompany them. The current study aims to find the main gestural strategies, used by the interlocutors in English political TV Interviews that represent speech acts. It is based on the hypothesis that there are different strategies of gestures used by interlocutors in political TV interviews that represent speech acts. The selected interviews have been analyzed in the light of an eclectic model based on model Kulkarni (2013) and Searle (1979). The first is used for analyzing the main kinds of body movements and types of gesticulation, and the latter for analyzing Searle's classification of speech acts since it is a pragmatic study. The results of the selected interviews have shown that gestural strategies are highly related to the context of situation. Each gesture performs a specific speech act. The interlocutors use gestural strategies to express a wide range of emotions, attitudes, approval, anxiety, disagreement, and affection. The participants in these interviews are equally conscious of their body language and verbal exchanges.